2017
DOI: 10.1093/bja/aex123
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane exposure for three hours triggers apoptotic cell death in neonatal macaque brain

Abstract: A 3 h exposure to ISO is sufficient to induce widespread neurotoxicity in the developing primate brain. These results are relevant for clinical medicine, as many surgical and diagnostic procedures in children require anaesthesia durations similar to those modelled here. Further research is necessary to identify long-term neurobehavioural consequences of 3 h ISO exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 36 publications
2
72
0
Order By: Relevance
“…A single three h exposure to isoflurane significantly increases apoptosis of both neurons and oligodendrocytes in infant rhesus monkeys. 11 Repeated exposures of infant rhesus monkeys to sevoflurane resulted in increased anxiety-related behaviours after an acute stressor. 41 Furthermore, multiple exposures to isoflurane anaesthesia for five h caused motor reflex deficits and anxiety behaviours compared with naïve and single isoflurane exposure groups.…”
Section: Investigations In Vivomentioning
confidence: 99%
“…A single three h exposure to isoflurane significantly increases apoptosis of both neurons and oligodendrocytes in infant rhesus monkeys. 11 Repeated exposures of infant rhesus monkeys to sevoflurane resulted in increased anxiety-related behaviours after an acute stressor. 41 Furthermore, multiple exposures to isoflurane anaesthesia for five h caused motor reflex deficits and anxiety behaviours compared with naïve and single isoflurane exposure groups.…”
Section: Investigations In Vivomentioning
confidence: 99%
“…The mechanistic pathways underlying these unwanted effects of isoflurane have not been clearly delineated, though several studies suggest its neurotoxic effects to be attributed to the activation of several apoptotic pathways that include caspase‐3 activation (Noguchi et al, ), ribosomal protein S6 inhibition (Li, Xue, Luo, Hu, & Yu, ), over‐activation of GSK3β (Tao et al, ), and the FASL‐FAS signaling pathway (Yi, Cai, & Li, ). Activation of these apoptotic pathways leads to impaired synaptogenesis, neuroinflammation, and subsequent learning and memory deficits.…”
Section: Introductionmentioning
confidence: 99%
“…Paule et al found that ketamine anesthesia for 24 hours led to long-term cognitive impairments in 7-dayold rhesus monkeys [19]. As shown in rodents, neonatal exposure to sevoflurane, isoflurane, nitric oxide, propofol, ketamine, and others was found to induce apoptosis of neurons and oligodendrocytes and long-term cognitive impairment in rhesus monkeys [10,[14][15][16][17][18][19][20][21][22]48]. Notably, a new important advance in this field was that recent findings showed that GA disrupted myelin formation in the developing brain of NHPs and mice [49,50].…”
Section: Advances In Nhpsmentioning
confidence: 97%
“…Among this research, a landmark study in this field showed that PND7 rats exhibited neuroapoptosis in a variety of brain regions and prolonged impairment in learning and memory after exposed to a commonly used anesthetic cocktail (N 2 O-midazolam-isoflurane) for 6 h [5]. Subsequent preclinical studies demonstrated that GA caused a vast amount of acute injury and long-term cognitive impairments in rodents [6][7][8][9][10][11][12][13] and nonhuman primates (NHP) [9,10,[14][15][16][17][18][19][20][21][22][23]. Even worse, exposure to GA in neonatal rodents produced adverse effects on the learning and memory of their offspring via epigenetic modulation [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%